The impact of minimum wages on medical expenditures and resource misallocation: evidence from China’s healthcare system - Yang, Chang; Sha, Chenbing; An, Tong (Frontiers in Public Health, 2025)
IntroductionWhile minimum wage policies are widely advocated for promoting health equity, empirical evidence on their impact on healthcare utilization remains limited. This study provides new evidence from China, where regional minimum wages interact with a hierarchical healthcare system characterized by resource imbalances.MethodsWe use large national hospital-level microdata from China to examine how regional minimum wages affect individual medical expenditures. To address endogeneity concerns, we employ an instrumental variable (IV) strategy using two-stage least squares (2SLS) estimation.ResultsThe IV estimates show that a one-yuan increase in the minimum wage raises outpatient spending per visit by 0.36 yuan, inpatient spending per admission by 7.90 yuan, and pharmaceutical spending per visit by 0.38 yuan. Mechanism analysis indicates three channels: higher demand for chronic disease management, greater use of treatment and surgery in inpatient care, and stronger preferences for higher-quality care, particularly in for-profit and tertiary hospitals.DiscussionWe find a dual impact of minimum wage increases on the hierarchical healthcare system: higher minimum wages strengthen the gatekeeping role of primary care but simultaneously intensify inpatient demand at higher-level hospitals and in resource-concentrated regions, thereby exacerbating resource misallocation and undermining efficiency.